Rapid weight loss habits before a competition in sambo athletes. - Figlioli, F.; Bianco, A.; Thomas, E.; Stajer, V.; Korovljev, D.; Trivic, T.; Maksimovic, N.; Drid, P. (Nutrients, 2021)
Background: Like other combat sports, sambo has competition rules that divide athletes into categories based on gender, age and weight. Athletes in combat sports often resort to rapid weight loss (RWL) methods to be more competitive in lower weight categories and gain an advantage against lighter, smaller and weaker competitors. The aim of this study was to examine the methodology implemented by two different sambo age categories, junior and senior athletes, in order to attain RWL. Methods: The sample consisted of 103 male sambo elite athletes (seniors/juniors: age 28.5 ± 4.3/18.9 ± 0.8; height (m): 1.7 ± 0.1/1.8 ± 0.1; weight (kg): 76.3 ± 17.8/74.4 ± 16.3; BMI (kg/m2): 25.0 ± 3.8/23.7 ± 3.9) who completed a survey on RWL. Results: Athletes reported losing a mean of 5 kg starting approximately 12 days before a competition. The most common methodology reported by senior and junior sambo athletes was gradually increasing dieting, followed by sauna and plastic suit training. Less common methods adopted were laxatives, diuretics, the use of diet pills and vomiting. There were significant group differences for sauna and diet pill ingestion. Coaches and parents are influential people in the lives of athletes concerning the weight loss strategy to be adopted. Conclusions: This study`s results unequivocally confirm the prevalent practice of RWL in both senior and junior sambo athletes. Although athletes prevalently chose "less harmful" methods, there is a need to inform parents and coaches of the risks and benefits of RWL.